PROBLEMATIKA DALAM PEMULIHAN HAK KORBAN PENGANIAYAAN OLEH MANTAN PACAR PENYANDANG DISABILITAS - Gabryella; Gladys Donna Karina; Hengki; Maysarah; Retno Ayu Tri Wahyuni; Rimayun Matippanna; Septian Adi Nugraha (JIL : Journal of Indonesian Law, 2025)
This study examines theproblems of restoring the rights of victims of criminal abuse committedby former boyfriends with disabilities through a case study in Yogyakarta.In the context of the Indonesian criminal justice system, which still tends to beperpetrator-centric, victims often experience secondary victimization due tothe lack of adequate legal protection. Through an empirical legal approachand critical victimology perspective analysis, this study shows that the fulfillment ofvictims’ rights is in line with the authority of law enforcement agencies,namely the police and the prosecutor’s office. However, from a critical victimology perspective,victims’ rights are still not fully fulfilled in this assault case, where law enforcement agencies themselves tend to be indifferentto the psychological condition and other factors. Law enforcement agencies only focuson fulfilling their duties rigidly in accordance with the law or standard operating procedures (SOPs).